DILEMA INDEPENDENSI AUDITOR SATUAN PENGAWASAN INTERNAL PERGURUAN TINGGI: STUDI FENOMENOLOGI - Syarif Syahrir Malle; Alimudidin Alimudidin; Nirwana Nirwana (Media Riset Akuntansi, Auditing & Informasi, 2019)
This research is motivated by a "unique" phenomenon from of the role of the profession internal auditors. For Internal auditors of  Internal Control Unit (SPI) in a non-profit organization, especially in an Higher Education Institution, the uniqueness has the potential to place it in a situation of independence dilemma. The purpose of this study is to understand the reality of the independence dilemma faced by SPI auditors as a result of the conditions and work environment. In order to explore the auditor's understanding of SPI, phenomenology is employed as methodology, under interpretive paradigm as the umbrella of this research. Exploration of understanding and awareness is done using Epoche. The results of the study revealed that the SPI auditor faced a situation of independence in various forms: (1) the negative auditing stigma in the form of the awarding of "kambing hitam" to SPI raises a dilemma for auditors and disturbs the working spirit of the SPI auditor, on the other hand if implemented improperly will be contrary to the obligation and further aggravate the negative stigma already attached; (2) there is a phenomenon of impropriety (abuse) on audit guidelines that has not been fully implemented and not evaluated to provide ethical consideration in the future; (3) the existence of obedience pressure in the form of "suspension" the rector signs the SPI examination report. due to the term audit conception that has not been agreed upon.